Stocking Up on Wealth . . . Concentration - Blair Fix (Real-World Economics Review, 2024)
It turns out that like the rest of us, billionaires experience wealth inequality. (Individuals who top the Forbes billionaire list are far richer than those at the bottom of the list.) Interestingly, this billionaire wealth concentration fluctuates over time … in tight correlation with the movement of the stock market. Why? A plausible reason — explored here – is that stock indexes like the S&P 500 are unwitting indicators of corporate concentration. And corporate concentration, in turn, seems to drive the concentration of individual wealth.
Keywords: P; P1; P12; P14; G3; G34; L1; 330; corporation; distribution; mergers & acquisitions; ownership; stock market; United States